AKTUALISASI HADIS-HADIS AKHLAK DALAM MERESPONS FENOMENA CYBERBULLYING DAN HATE SPEECH DI MEDIA SOSIAL - Alpen Pinem; M. Syukri Azwar Lubis (Jurnal Bilqolam Pendidikan Islam, 2025)
The digital era and the widespread use of social media have transformed the global communication landscape, yet on the other hand, they have triggered an escalation of digital social pathology phenomena such as cyberbullying and hate speech. This article aims to examine the contextualization and actualization of the moral hadiths (prophetic traditions) of the Prophet Muhammad (PBUH) as a normative and preventive instrument in addressing the ethical crisis in cyberspace. Using a qualitative research method based on library research with a sociological-textual approach, this study analyzes hadiths related to the prohibition of insulting others, guarding one's tongue, and the obligation to spread peace. The findings indicate that concepts such as Hifzh al-Lisan (guarding the tongue/fingers), the prohibition of Takhrib (damaging reputation), and the obligation of Kafful Adza (refraining from harming others) are highly relevant for transformation into digital ethics (netiquette). The actualization of these moral hadiths not only serves as a form of individual moral control (digital piety) but also as a complementary preventive solution to the existing positive laws.